PowerPoint 2016 For Dummies - Lowe, Doug.; Lambert, Joan. (PHI, Dummies A Wiley Brand, 2016)
Experience learning made easy-and quickly teach yourself how to create dynamic presentations with PowerPoint 2010. With STEP BY STEP, you set the pace-building and practicing the skills you need, just when you need them! Topics include creating great-looking slides using templates or your own designs; creating sophisticated charts and diagrams; using animation, sound, and other special effects; creating presentations simultaneously with others over the Web; delivering presentations; and other core topics.